2016
DOI: 10.3847/1538-4357/833/2/181
|View full text |Cite
|
Sign up to set email alerts
|

Constraints of the Physics of Low-Mass Agb Stars From Ch and Cemp Stars

Abstract: We analyze a set of published elemental abundances from a sample of CH stars which are based on high resolution spectral analysis of ELODIE and SUBARU/HDS spectra. All the elemental abundances were derived from local thermodynamic equilibrium analysis using model atmospheres, and thus, they represent the largest homogeneous abundance data available for CH stars up to date. For this reason, we can use the set to constrain the physics and the nucleosynthesis occurring in low mass AGB stars. CH stars have been po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 95 publications
2
67
0
1
Order By: Relevance
“…The abundance results presented here will add to the abundance data obtained from our previous studies in a homogeneous manner and compiled in Cristallo et al (2016), that can be used to constrain the physics and the nucleosynthesis occuring in low-mass AGB stars. Abundance results of CEMP-r/s stars will provide observational constrains for theoretical studies of i-process, suggested in the recent years for the origin of CEMP-r/s stars.…”
Section: Resultsmentioning
confidence: 84%
“…The abundance results presented here will add to the abundance data obtained from our previous studies in a homogeneous manner and compiled in Cristallo et al (2016), that can be used to constrain the physics and the nucleosynthesis occuring in low-mass AGB stars. Abundance results of CEMP-r/s stars will provide observational constrains for theoretical studies of i-process, suggested in the recent years for the origin of CEMP-r/s stars.…”
Section: Resultsmentioning
confidence: 84%
“…As a consequence, the H-burning shell possibly switches off, allowing the convective envelope to penetrate in regions where heavy isotopes have been freshly synthesized. As already highlighted, the main neutron sources is the 13 C(α,n) 16 O reaction. In order to obtain a sufficient amount of 13 C for the activation of the s-process, protons from the envelope have to be mixed (with a low efficiency) with the 12 C-rich material in the underlying radiative zone.…”
Section: The S-process In Low and Intermediate Mass Starsmentioning
confidence: 89%
“…The different s-process trends as a function of the initial metallicity are reported in the left panel of Figure 3. Major neutron sources in stars are the 13 C(α,n) 16 O and the 22 Ne(α,n) 25 Mg reactions. While the number of iron seeds directly scales with metallicity, the number of neutrons may have a primary behavior, that is it may be a direct product of H-and He-burning.…”
Section: The Theory Of the S-processmentioning
confidence: 99%
See 1 more Smart Citation
“…Several effects play a role in fixing the extension of the TDUP, like extra diffusion of protons termed "overshooting" (see discussion in ( [8]), [2], [4]), rotationally-induced mixing ( [11]), or a recent attempt considering the effect of mixing by magnetic buoyancy in the framework of magnetohydrodynamics ( [20]). More work is needed to better understand mixing processes during the AGB phases of stars.…”
Section: S-process Stellar Sitementioning
confidence: 99%